Estimated Prevalence of Glaucoma in South Korea Using the National Claims Database - Sang Jin Seo; Yun Ha Lee; Sang Yeop Lee; Hyoung Won Bae; Samin Hong; Gong Je Seong; Chan Yun Kim (Journal of Ophthalmology)
Purpose. To estimate the prevalence of glaucoma and costs associated with glaucoma care in South Korea between 2008 and 2013 using the Korean national claims database. Design. Retrospective cross-sectional study from a national claims database. Methods. Patients who were diagnosed with glaucoma between 2008 and 2013 were retrospectively identified in the national claims database using glaucoma diagnostic codes. For each year, the prevalence of glaucoma and direct medical costs associated with glaucoma care were estimated. Result. The prevalence of glaucoma in patients ≥40 years of age increased from 0.79% in 2008 to 1.05% in 2013. The number of patients with glaucoma increased by 54% between 2008 and 2013 (9% average annual increase). The prevalence of glaucoma increased with age and was higher in males than in females. The cost to care for glaucoma patients increased from $16.5 million in 2008 to $29.2 million in 2013, which translated into an 81% increase over the 6 years examined (12.7% average annual increase). Conclusion. The estimated prevalence and socioeconomic burden of glaucoma have steadily increased each year in South Korea. Nevertheless, many glaucoma patients remain undiagnosed in the present study using national claims database.